2016
DOI: 10.1097/der.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Dust Mite Sensitivity and Atopic Dermatitis

Abstract: Patch testing to DM does not seem to have clinical use for determining the etiology of dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
2
3
1
Order By: Relevance
“…60 The ability of HDM antigens to elicit APT reactions in a high frequency of individuals makes it a valuable tool to study cutaneous hypersensitivity. 10 In our study,~55% of individuals without AD had positive HDM responses and~40% of individuals with AD had positive HDM reactions, similar to prior reports. 61,62 While allergic sensitivity to HDM is highly based on elevated HDM-specific IgE levels, many studies have not found associations between IgE levels and APT reactivity in atopic individuals.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…60 The ability of HDM antigens to elicit APT reactions in a high frequency of individuals makes it a valuable tool to study cutaneous hypersensitivity. 10 In our study,~55% of individuals without AD had positive HDM responses and~40% of individuals with AD had positive HDM reactions, similar to prior reports. 61,62 While allergic sensitivity to HDM is highly based on elevated HDM-specific IgE levels, many studies have not found associations between IgE levels and APT reactivity in atopic individuals.…”
Section: Discussionsupporting
confidence: 91%
“…HDM is ubiquitous in the environment, and many individuals are sensitized to its associated protein antigens Der p1/2 . The ability of HDM antigens to elicit APT reactions in a high frequency of individuals makes it a valuable tool to study cutaneous hypersensitivity . In our study, ~55% of individuals without AD had positive HDM responses and ~40% of individuals with AD had positive HDM reactions, similar to prior reports …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations